Transcranial Direct Current Stimulation and Mirror Therapy for Neuropathic Pain After Brachial Plexus Avulsion: A Randomized, Double-Blind, Controlled Pilot Study - Ferreira, Clarice Martins; de Carvalho, Carolina Dias; Gomes, Ruth; Bonifácio de Assis, Erickson Duarte; Andrade, Suellen Marinho (Frontiers in Neurology, 2020)
Introduction: Although transcranial direct current stimulation (tDCS) and mirror therapy (MT) have benefits in combating chronic pain, there is still no evidence of the effects of the simultaneous application of these techniques in patients with neuropathic pain. This study aims to assess the efficacy of tDCS paired with MT in neuropathic pain after brachial plexus injury. Methods: In a sham controlled, double-blind, parallel-group design, 16 patients were randomized to receive active or sham tDCS administered during mirror therapy. Each patient received 12 treatment sessions, 30 min each, during a period of 4 weeks over M1 contralateral to the side of the injury. Outcome variables were evaluated at baseline and post-treatment using the McGill questionnaire, Brief Pain Inventory, and Medical Outcomes Study 36 - Item Short-Form Health Survey. Long-term effects of treatment were evaluated at a 3-month follow-up. Results: Results: An improvement in pain relief and quality of life were observed in both groups (p≤ 0.05). However, active tDCS and mirror therapy resulted in greater improvements after the endpoint (p≤0.02). No statistically significant differences in the outcome measures were identified among the groups at follow-up (p≥0.12). A significant relationship was found between baseline pain intensity and outcome measures (p≤0.04). Moreover, the results showed that state anxiety is closely linked to post-treatment pain relief (p≤0.05). Conclusion: Active tDCS combined with mirror therapy has a short-term effect of pain relief, however, levels of pain and anxiety at the baseline should be considered.